1979
DOI: 10.1161/01.hyp.1.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in pressure, volume and renin interrelationships in essential hypertension.

Abstract: SUMMARYThe interrelationships of arterial pressure, plasma volume (PV), and plasma renin activity were studied in 152 consecutive male patients with uncomplicated essential hypertension. Of these, 22 (17 white and 5 black) subjects had normal plasma volumes and because of tbe small number were not included in the analysis of results. Tbe remaining 130 (35 black and 95 white) patients were classified as having either expanded or contracted plasma volume. A higher percentage of black (43%) than white (21%) subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…If a two-drug combination does not work, other drugs from a different class should be added until blood pressure reaches the expected goal. With respect to treatment of black hypertensive patients, who are, usually, resistant to monotherapy with ARBs or ACEIs because they are low renin hypertensives, 87 the addition of a diuretic to an ARB or ACEI, eliminates this difference and black patients respond to these regimens similarly to whites. 88 Hypertensive patients with type II diabetes mellitus and diabetic nephropathy should preferably be treated with ARBs according to the recommendations of the American Diabetes Association.…”
Section: Heart Failurementioning
confidence: 99%
“…If a two-drug combination does not work, other drugs from a different class should be added until blood pressure reaches the expected goal. With respect to treatment of black hypertensive patients, who are, usually, resistant to monotherapy with ARBs or ACEIs because they are low renin hypertensives, 87 the addition of a diuretic to an ARB or ACEI, eliminates this difference and black patients respond to these regimens similarly to whites. 88 Hypertensive patients with type II diabetes mellitus and diabetic nephropathy should preferably be treated with ARBs according to the recommendations of the American Diabetes Association.…”
Section: Heart Failurementioning
confidence: 99%
“…For the purposes of that study, 14 plasma volume exceeding 19.0 ml/cm was considered arbitrarily to be "expanded" plasma volume, and any level of plasma volume less than 17.0 ml/cm was considered arbitrarily to be "contracted" plasma volume. There were 22 patients (17 white and 5 black) whose plasma volume was found to be normal (i.e., 18.0±0.9 ml/cm), and because of the small number in this group, they were excluded from the analysis.…”
Section: Intravascular Volume and Plasma Renin Activitymentioning
confidence: 99%
“…Hence, there is a segment of black patients with essential hypertension in whom arterial pressure, intravascular volume, and plasma renin activity do not demonstrate the normal interrelations among these three variables that were found in white patients, and these black patients seemed to be more volume dependent for any level of arterial pressure (Table 2). 14 …”
Section: Intravascular Volume and Plasma Renin Activitymentioning
confidence: 99%
“…[21] However, certain populations, like AfricanAmericans, are resistant to drugs that block the renin-angiotensin-aldosterone system [RAAS], like ACE inhibitors and ARBs given as monotherapy, [22,23] because these drugs exert their major antihypertensive effects through the blockade of RAAS, and Black patients are usually low-renin and volume-dependent hypertensive subjects. [24] Several clinical trials have shown that the combination of ACE inhibitors with CCBs increases their hypotensive potency [11][12][13][14][15][16][17]25] because of a synergistic effect of inhibition of RAAS and a direct arterial dilatory effect, which is independent of RAAS inhibition. Most of the previous publications have used lower-dose ACE inhibitor-CCB combinations and did not specifically focus on the antihypertensive effects of these drug combinations on Black hypertensive patients compared with their White counterparts.…”
Section: Discussionmentioning
confidence: 99%